Biomimetic CuS nanoparticles for radiosensitization with mild photothermal therapy and GSH-depletion - Zhou, Xiaoxiang; Li, Xiang; Wu, Bo; Chen, Zhiran; Chen, Longyun (Frontiers in Oncology, 2022)
Due to its non-invasive and highly effective characteristics, radiotherapy has attracted significant interest in cancer treatment. However, radioresistance of solid tumors caused by a unique tumor microenvironment diminishes the therapeutic effect of cancer radiotherapy. To address this issue, we developed a nanoplatform for tumor-specific targeting to improve radiotherapy. Specifically, hollow CuS nanoparticles were decorated with the platelet cell membrane (PC), endowing this nanoplatform with the therapeutic property of navigating to the tumor region for glutathione (GSH)-depletion photothermal therapy. It was discovered that mild photothermal therapy mediated by PC ameliorated hypoxia in the tumor microenvironment. Meanwhile, GSH, which contributes to repairing radiotherapy-induced DNA double-strand breaks, was depleted by PC in an acidic microenvironment. Therefore, radioresistance could be diminished while cancer cell self-repair was prevented. At therapeutic doses, PC nanoparticles have negligible toxic effects on normal tissues. PC demonstrates promise for both in vivo and in vitro radiosensitization due to its GSH-depletion, photothermal efficiency, and tumor-specific properties.